A geografia no Ranking Universitário Folha 2019 - René Somain (Confins)
The ranking of Universities done by the Folha de S. Paulo is an annual evaluation of all Brazilian universities that uses national and international data and opinion polls to evaluate them in five aspects (research, teaching, marketing, internationalization and innovation). The focus here is on geography departments and using these data are developed maps of their overall grade, the grade given by the Ministry of Education and the grade given by the students who were trained there.